DU Pont System Analysis in Measuring Financial Performance of Mice Industry Companies in Indonesia (A Case Study on PT Dyandra Media International Tbk for the 2019-2023 Period) - Vania Yumna Ardita; Zulfa Irawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study conducts a DuPont system analysis to assess the financial performance of PT Dyandra Media International Tbk in the MICE industry in Indonesia from 2019 to 2023. Using a descriptive quantitative approach, the research analyzes key financial ratios, including Net Profit Margin (NPM), Total Asset Turnover (TATO), and Equity Multiplier (EM), derived from the company's financial statements. The study reveals significant financial fluctuations during the 2019–2021 period due to the impact of the COVID-19 pandemic, with a decline in profitability, asset utilization, and return on assets. However, recovery efforts in 2023 led to a notable improvement in Return on Equity (ROE) to 12.43%, driven by enhanced asset efficiency and cost management. The study recommends that PT Dyandra Media International Tbk focus on increasing operational efficiency, adopting technology, diversifying revenue streams, and maintaining prudent leverage management to mitigate financial risks. Strengthened financial planning is also crucial to navigating future uncertainties. The study suggests that future research could compare the company's performance with competitors in the MICE or tourism sectors and explore external factors through advanced methods such as big data analytics or qualitative approaches.